Pengaruh Penerapan Strategi Inkuiri dan Penggunaan Media Power Point terhadap Kreativitas Belajar Siswa pada Pelajaran Pendidikan Agama Islam - muhammad hidayat (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2020)
This study aims to see whether there is an influence of the Implementation of the Inkuri Strategy and the Use of Power Point Media on Student Learning Creativity in PAI Lessons in Private Vocational Schools in the Bukit Raya District of Pekanbaru City. The population in this study were all private vocational students in the Bukit Raya District of Pekanbaru, totaling 1,012 people. The sample in this study was taken by probality random sampling technique with 5% of the total pollution that is 290 people. Data collection was performed using a questionnaire technique (questionnaire), the data collected was analyzed using multiple regression analysis namely Y = a + b1X1 + b2 X2. The results of this study indicate the value of R2 (coefficient of determination) or R Square of 0.343 or 34.3%. This value can be interpreted that changes in student learning creativity by changing the value of the independent variable application of inquiry strategy and the use of power point media by 34.3% while 56.7% is determined by changes in other factors. The tcount for the implementation of the inquiry strategy variable was 7.856 with sig. 0,000 is smaller than 0.05, this means that there is an influence of the application of inquiry strategy on student learning creativity and the tcount for the variable use of power point media is 4.742 with sig. 0,000 is less than 0.05 which means there is an influence of the use of power point media on student learning creativity. It can be concluded that there is an influence between the application of inquiry strategy and the use of power point media on the creativity of student learning in PAI lessons in Private Vocational Schools in the Bukit Raya District of Pekanbaru City